Menuju Inklusi Tenaga Kerja Penyandang Disabilitas: Implementasi Program Pengabdian di Yayasan Peduli Anak Cacat Malang - Ariska Zakiyatul Bariroh; Fildza Shabrina Dias Alifiyah; Aida Najma Chumaira; Ermanto Fahamsyah; Rahmadi Indra Tektona (LP2M Universitas Ibrahimy, 2024)
Yayasan Peduli Anak Cacat (YPAC) Malang is a non-profit organization that aims to provide services to children with disabilities. This community service program in partnership with YPAC Malang aims to improve the inclusion of the disabled workforce in the YPAC Malang environment through various efforts, including skills training, socialization, and the creation of a Special Employment Contract. The research method used in this service program uses a PAR (Participatory Action Research) based approach. Through the involvement of YPAC Malang partners, companies, academics, and government, this program aims to provide legal protection, equality, and employment opportunities for people with disabilities. Although faced with various challenges, such as limited company partners and labor classification mismatches, this program is expected to have a significant positive impact on people with disabilities and society as a whole.